COMPARISON OF PHYSICAL CHARACTERISTICS OF VANISHING CREAM BASE, COW GHEE AND SHATA-DHAUTA-GHRITA AS PER PHARMACOPOEIAL STANDARDS - RAVINDRA R.P.; PATA MUSLIM K. (International Journal of Pharma and Bio Sciences, 2013)
Modern formulation science requires all excipients to be inert and to conform to Pharmacopoeial standards. However, Ayurveda, the ancient science of health from India believes that all substances possess therapeutic actions. Modern formulators have a choice of choosing from the modern formulation bases (e.g.; vanishing cream base) or Ayurvedic bases (e.g.; cow ghee) while formulating an herbal product. Nonetheless, all such bases must conform to specifications of physico-chemical properties that have the potential to affect the efficacy/ safety/stability of the product. In this study, we have compared the physical characteristics of a modern base (vanishing cream) with two Ayurvedic bases (clarified butter fat -cow ghee and Shata-dhauta-ghrita). Shata-dhauta-ghrita (SDG) is prepared by washing cow ghee 100 times with water and is prescribed for treatment of wounds, burns etc. All three bases were evaluated for their pH, viscosity, spreadability, organoleptic properties, globule size, acid value, saponification value, peroxide value, ester value, iodine value and free fatty acids. It was found that while cow ghee and vanishing cream base had comparable characteristics, SDG exhibits a much less degree of unsaturation (suggesting better physico-chemical stability) and better consistency (and hence suitability for topical applications). The paper also suggests the possible mechanism for improvement of these characteristics in the process of conversion of cow ghee to SDG. It further suggests that SDG might be a potential candidate as a base for topical preparations, esp. for wounds and burns.